ALADIN‐α—An open‐source MATLAB toolbox for distributed non‐convex optimization. (22nd November 2021) - Engelmann, Alexander; Jiang, Yuning; Benner, Henrieke; Ou, Ruchuan; Houska, Boris; Faulwasser, Timm
Abstract: This article introduces an open‐source software for distributed and decentralized non‐convex optimization named ALADIN‐ α . ALADIN‐ α is a MATLAB implementation of tailored variants of the Augmented Lagrangian Alternating Direction Inexact Newton (ALADIN) algorithm. It is user interface is convenient for rapid prototyping of non‐convex distributed optimization algorithms. An improved version of the recently proposed bi‐level variant of ALADIN is included enabling decentralized non‐convex optimization with reduced information exchange. A collection of examples from different applications fields including chemical engineering, robotics, and power systems underpins the potential of ALADIN‐ α .